2007
DOI: 10.1007/s10616-006-9041-4
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle phase dependent productivity of a recombinant Chinese hamster ovary cell line

Abstract: A Chinese Hamster Ovary cell line, CHO1-15 500 , producing recombinant human tissue type plasminogen activator (tPA) via the dihydrofolate reductase (DHFR) amplification system, was studied in batch culture. In this system both DHFR and tPA are under the control of the strong constitutive viral SV40 early promoter. Employing the cumulative viable cell-hour approach, the specific productivity of tPA had maxima in the lag (0.065 pg cell -1 h -1 ) and early decline (0.040 pg cell -1 h -1 ) population growth phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 51 publications
(59 reference statements)
1
17
1
Order By: Relevance
“…S and G 2 /M) to the total productivity. A similar outcome is observed if the productivity is evaluated in terms of the cumulative cell hours [68] and the analysis is broken down per cell cycle phase [10]. Both a partially growth associated productivity and a better correlation towards the G 1 /G 0 phase is observed.…”
Section: Discussionsupporting
confidence: 67%
“…S and G 2 /M) to the total productivity. A similar outcome is observed if the productivity is evaluated in terms of the cumulative cell hours [68] and the analysis is broken down per cell cycle phase [10]. Both a partially growth associated productivity and a better correlation towards the G 1 /G 0 phase is observed.…”
Section: Discussionsupporting
confidence: 67%
“…Depletion of glutathione with BSO has been shown to arrest cell division, suggesting that de novo glutathione synthesis is required for progression through the cell cycle and results in increased cell size . It has been reported that in CHO‐K1‐15 500 permanently producing tPA, cell size is a major determinant of productivity . However, this observation was not replicated in clones derived from a CHOK1SV pool transiently expressing cB72.3 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, product data plotted against the respective cumulative volumetric cell hours allowed for the characterization of protein production kinetics [11]. For example, Fig.…”
Section: Resultsmentioning
confidence: 99%